The Aesthetics of Middlebrow Fiction - Perrin, Tom. author. aut Link
IX, 197 p.
Keywords: During the Cold War, many popular American novels were labelled "middlebrow," leading to a general belief that these texts held less intellectual merit. Perrin debunks these unfair assumptions through works by James Michener, Harper Lee, and Leon Uris, arguing that such writers made a major contribution to the tradition of American literature.